Targeted treatment approaches and pathogenicity of antibody subclasses in MuSK-myasthenia gravis - Cao, M (2021)
Muscle Specific Kinase myasthenia gravis (MuSK-MG) is an autoimmune disease that impairs neuromuscular transmission leading to muscle fatigability. No targeted medications are currently available, and non-specific immunotherapies are required. MuSK initiates a phosphorylation cascade regulating the clustering of acetylcholine receptors (AChRs) at the neuromuscular junction (NMJ). SH2 domain-containing phosphatase (SHP2) negatively regulates the pathway inhibiting MuSK activation. In MuSK-MG, monovalent IgG4 autoantibodies block MuSK phosphorylation dispersing AChR clusters. The role of the smaller population of divalent MuSK IgG1, 2 and 3 antibodies is still undefined. The aims of the study were a) to test in vitro and in vivo SHP2 inhibition by NSC-87877 evaluating its efficacy in counteracting the effects of MuSK-Abs; b) to investigate the pathogenic contribution of MuSK IgG1-3-Abs.